Aktualisasi Nilai Kebangsaan dalam Sistem Pendidikan di Pondok Pesantren Idrisiyah Tasikmalaya - Nurhuda, Dede Yuda Wahyu (Penerbit Widina, Widina Media Utama, 2025)
Indonesia as a nation state has characteristics that are rich in values that live in its society. These values need to be well maintained by all components of the nation. Today, Indonesia is tested with various problems in the midst of society. The world of education is a very important place as a means of maintaining and preserving national values. Pesantren as one of the places where education is carried out which is characteristic of the Indonesian nation, is an important means in instilling national values, and with research looking for an overview of the implementation of the cultivation of national values in the pesantren education system. The research method used is descriptive research method with qualitative approach. The data is in the form of information in detail explaining the description of the actualisation of the application of national values through interviews and field studies conducted, from the data obtained, analysis is carried out to obtain an overview of the implementation of national values. The results showed that the actualisation of national values at the Idrisiyah Islamic Boarding School was carried out well, the systematic curriculum was in accordance with the provisions, supported by activities and supporting programs. The characteristics of Islamic Education carried out in the Islamic Boarding School are the main means in instilling national values, the Islamic Boarding School which was born from the Idrisiyah Order adds to the strength of the cultivation of national values, especially the value of love for the homeland.ABSTRAKIndonesia sebagai negara bangsa memiliki karakteristik yang kaya akan nilai yang hidup dalam masyarakatnya. Nilai-nilai tersebut perlu dijaga dengan baik oleh seluruh komponen bangsa. Negara Indonesia hari ini diuji dengan berbagai permasalahan ditengah-tengah masyarakat. Dunia Pendidikan menjadi salah satu wadah yang sangat penting sebagai sarana mempertahankan dan melestarikan nilai kebangsaan. Pesantren sebagai salah satu tempat dilaksanakan Pendidikan yang menjadi ciri khas dari bangsa Indonesia, menjadi sarana yang penting dalam menanamkan nilai kebangsaan, dan dengan penelitian mencari Gambaran implementasi penanaman nilai kebangsaan dalam system Pendidikan pesantren. Metode penelitian yang digunakan adalah metode penelitian deskriptif dengan pendekatan kualitatif. Data berupa informasi secara rinci menjelaskan gambaran tentang aktualisasi penerapan nilai kebangsaan melalui wawancara dan studi lapangan yang dilakukan, dari data yang didapatkan dilakukan analisis untuk mendapatkan gambaran pelaksanaan nilai kebangsaan. Hasil penelitian menunjukan bahwa aktualisasi Nilai-nilai kebangsaan di Pondok Pesantren Idrisiyah, dilakukan dengan baik, sistematika kurikulum sesuai dengan ketentuan, didukung dengan aktivitas dan program penunjang. Karakteristik Pendidikan Keasramaan yang dilaksanakan di Pesantren menjadi sarana utama dalam menanamkan nilai kebangsaan, Pesantren yang lahir dari Tarekat Idrisiyah menambah kokoh penanaman nilai-nilai kebangsaan, terutama nilai kecintaan terhadap tanah air.